Kontroversi Dakwah Fethullah Gulen: Golden Generation dan Infiltrasi ke dalam Lembaga Negara - Akhmad Rizqon Khamami (Universitas Darussalam Gontor, 2019)
AbstractThis article examines the source of Fethullah Gulen's controversy in his da’wah, that is golden generation and their infiltration into state institutions. Golden generation is the main goal of Gulen's mission. He creates golden generations through his educational activities. He founded schools, dormitories and isik evler. After undergoing training, golden generations are urged to pursue their further education in top universities. Afterwards, they are encouraged to pursue careers in any state institutions. Facts have it, Gulen succeeded in placing the golden generation in all state institutions, including the police, prosecutors, judiciary and military institutions. They reach some high posts in the state institution. This very way is Gulen’s method to ‘Islamize the persons of the state institutions’ rather than to ‘Islamize the institution’. Later on this very method and bringing the golden generation into the state institutions give birth to a controversy that culminated in the 2016 Turkish coup. This article concludes that the coup is originated from Gulen's concept of the golden generation and his encouragement for the golden generations to take into state institutions and carry out 'Islamization' from within the institution. Keywords: Gulen Movement, Gulen’s da’wah, Gulen’s controversy, golden generation, infiltration. AbstrakArtikel ini mengupas sumber kontroversi dakwah Fethullah Gulen, yaitu keterkaitan antara golden generation dengan infiltrasi mereka ke dalam lembaga negara. Pembentukan golden generation merupakan tujuan utama dakwah Gulen. Ia mencetak golden generation melalui aktivitas pendidikan. Gulen mendirikan sekolah, asrama dan isik evler. Setelah menjalani penggemblengan, diharapkan golden generation akan menembus universitas papan atas. Mereka selanjutnya didorong untuk berkarir di lembaga negara. Terbukti, Gulen berhasil menempatkan golden generation pada semua lembaga negara, antara lain lembaga kepolisian, kejaksaan, kehakiman dan militer. Mereka menempati pos-pos penting di lembaga negara tersebut. Cara Gulen ini merupakan metode dakwah Gulen yang hendak ‘mengislamkan pemegang lembaga’, bukan ‘mengislamkan lembaga’. Kelak metode dakwah dengan cara menempatkan golden generation ke dalam lembaga negara ini melahirkan kontroversi yang berpuncak pada kudeta Turki 2016. Artikel ini menyimpulkan bahwa kudeta tersebut sesungguhnya bersumber dari konsep Gulen tentang golden generation dan aktivitas dakwah Gulen yang mendorong golden generation tersebut untuk berkiprah di lembaga-lembaga negara dan melakukan ‘Islamisasi’ dari dalam lembaga. Kata kunci: gerakan Gulen, dakwah Gulen, kontroversi Gulen, generasi emas, infiltrasi.